2011
DOI: 10.3390/cancers3044024
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Delivery of Natural Products in the Prevention and Treatment of Cancers: Current Status and Future Prospects

Abstract: The advent of nanotechnology has had a revolutionary impact on many aspects of 21st century life. Nanotechnology has provided an opportunity to explore new avenues that conventional technologies have been unable to make an impact on for diagnosis, prevention, and therapy of different diseases, and of cancer in particular. Entities in nanometer sizes are excellent platforms to incorporate various drugs or active materials that can be delivered effectively to the desired action site without compromising the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 98 publications
(105 reference statements)
0
63
1
Order By: Relevance
“…Many active principles derived from natural compounds have powerful chemopreventive activities in diseases. 4 Active principles from natural sources with anti cancer properties exhibit their activities via apoptotic and cell-signaling pathways, and act Although natural products have strong therapeutic values, many of their derivatives have poor water solubility and bioavailability, which severely limit their use in medicine. 6 The nanoparticle delivery systems are newly introduced methods to overcome these limitations, turning potential but poorly soluble drugs into effective therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many active principles derived from natural compounds have powerful chemopreventive activities in diseases. 4 Active principles from natural sources with anti cancer properties exhibit their activities via apoptotic and cell-signaling pathways, and act Although natural products have strong therapeutic values, many of their derivatives have poor water solubility and bioavailability, which severely limit their use in medicine. 6 The nanoparticle delivery systems are newly introduced methods to overcome these limitations, turning potential but poorly soluble drugs into effective therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…8 Natural product nanoparticles with anticancer properties offer considerable advantage over currently employed chemopreventive and chemotherapeutic approaches in the treatment of cancers. 4 Nanocarriers are nanosized materials (1-100 nm) that can carry multiple drugs or compounds. Nanocarriers can also be used to increase local drug concentration by the incorporation of drugs while facilitating controlled release at the targets.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve maximum therapeutic efficiency of anticancer poorly water-soluble compounds a novel approaches are needed [28]. Among proposed strategies, the nanotechnology is examined to solve the inherent problems such as solubility, stability, toxicity, delivery and bioavailability [29]. Various organic nanocarriers for enhancing the solubility and delivery of Cur, including PLGA nanoparticles, nanosuspensions, cyclodextrin complexation, polymeric nanoparticles liposomes were tested.…”
Section: Introductionmentioning
confidence: 99%
“…36 More recently, these approaches are being exploited in cancer prevention with dietary phytochemicals. [37][38][39] As a result, a new area of investigation, nanochemoprevention, was born which holds promise to enhance the efficacy of bioactive food compounds through nanoencapsulation. In fact, recent studies showed that nanoprototypes of epigallocatechin-3-gallate (EGCG) from green tea, curcumin from turmeric, and resveratrol from table grapes are more efficacious than their free counterparts.…”
mentioning
confidence: 99%